Kostis Kornetis, Eirini Kotsovili and Nikolaos Papadogiannis, eds. Consumption and Gender in Southern Europe since the Long 1960s - Gomez-del-Moral, Alejandro Jose (Historein, 2018)
Kostis Kornetis, Eirini Kotsovili, and Nikolaos Papadogiannis, eds. Consumption and Gender in Southern Europe since the Long 1960s. London: Bloomsbury Academic, 2016. xvi + 280 pp.